1996
DOI: 10.1152/ajpregu.1996.271.1.r200
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic angiotensin hypertension: neural and nonneural components, time course, and dose dependency

Abstract: We examined the mechanisms mediating hypertension in conscious rats during acute and chronic infusion of angiotensin II (ANG II) at pressor doses (50, 100, and 200 ng.kg-1.min-1). Trimethaphan-induced blood pressure reduction was inversely related to the acute dose of ANG II, consistent with a constrictor action of ANG II on vascular smooth muscle and withdrawal of sympathetic tone. During chronic ANG II infusion, the entire increase in mean arterial pressure (MAP) was inhibited by trimethaphan, consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
84
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 0 publications
6
84
2
Order By: Relevance
“…Blood-borne Ang II is known to produce a long-term hypertensive response by both peripheral and brain mechanisms [20][21] . Since the hypertensive effect of combined treatment with Ang II and TMAO appeared after 5 days of infusions, it may be hypothesized that the effect was caused rather by long-term Ang II-dependent mechanisms such as an increase in blood volume or an increase in sympathetic drive due to the activation of central mechanisms involved in BP control 13,21 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood-borne Ang II is known to produce a long-term hypertensive response by both peripheral and brain mechanisms [20][21] . Since the hypertensive effect of combined treatment with Ang II and TMAO appeared after 5 days of infusions, it may be hypothesized that the effect was caused rather by long-term Ang II-dependent mechanisms such as an increase in blood volume or an increase in sympathetic drive due to the activation of central mechanisms involved in BP control 13,21 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Since the hypertensive effect of combined treatment with Ang II and TMAO appeared after 5 days of infusions, it may be hypothesized that the effect was caused rather by long-term Ang II-dependent mechanisms such as an increase in blood volume or an increase in sympathetic drive due to the activation of central mechanisms involved in BP control 13,21 . This notion may also be supported by our preliminary experiments in which we found that short, 30-seconds-long IV infusions of TMAO at a dose of 1 to 12 mmol × s -1 did not affect resting BP and hypertensive effects of Ang II in rats (data not presented).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…To address this question, we used intravenous administration of a hypertensive concentration of ANG II and ganglionic blockade with trimetaphan because these techniques have been previously used to evaluate the contribution of SNS stimulation to the pressor response evoked by ANG II (6,25).…”
mentioning
confidence: 99%
“…Systemic ANG II has been implicated in chronically increased blood pressure through several mechanisms, including activation of the SNS (25,48). Although the initial increase in blood pressure during peripheral administration of pressor concentrations of ANG II is due to the direct vasoconstrictor effects of the hormone on vascular smooth muscle, the chronic hypertensive response to longer-term, continuous administration (hours to days) of ANG II is mediated by progressive activation of the SNS (6,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation